Job satisfaction’s role in mediating employer branding’s influence on the intention to leave for Indonesian customs: Moderated by job rotation (International Journal of Management and Sustainability, 2025)
This research aims to determine the role of satisfaction in mediating the influence of employer branding on the intention to leave Indonesian Customs, which is moderated by job rotation. The population of this research consists of all employees, currently totaling 16,062. The sampling method utilized is probability sampling. Given the large population spread across various regions, the chosen sampling technique is Proportional Random Sampling, in which a sample is taken proportionally from the population. This quantitative research employed a questionnaire involving 391 respondents from 79 Indonesian Customs Offices and utilized SEM-PLS for analysis. The findings show that job satisfaction mediates the effect of employer branding on the intention to leave. Additionally, Customs employees' intention to leave is influenced by employer branding and job satisfaction, as well as job rotation, which significantly moderates the influence of employer branding on the intention to leave. This research enriches Social Identity Theory and Traditional Turnover Theory by explaining the relationship between employer branding and employee intention to leave. It also enhances the literature regarding the importance of employer branding in organizations related to turnover intentions. Finally, it highlights that the success of job rotation moderates the relationship between employer branding and the intention to leave, which is a new finding in this research and has yet to be discovered. Organizations may use these findings to reduce turnover intentions by implementing appropriate employer branding and job rotation strategies to increase employee job satisfaction.